The Spectre of Death in Don DeLillo’s Zero K - Lovro Furjanić (Anafora, 2019)
This paper offers a basic overview of the transhumanist movement, particularly its approach to ageing. The transhumanist philosophy of ageing strives both towards prolonging the human life and removing the ill effects of ageing. Special emphasis will be put on cryopreservation, which is a currently relevant and functional, albeit controversial, method of suspending death. A group of traditional issues regarding cryonic technology, such as its biological feasibility, will be evaluated. Following the detailed theoretical investigation, Don DeLillo’s Zero K will be analyzed based on the philosophical background of the transhumanist movement, the evaluation of the desirability of cryonic technology, and its rendering of ageing and death. Zero K subtly brings to attention the economic background of this complex technical process, which is often a blind spot in discussions regarding the positive and negative aspects of cryonics. Transhumanism espouses the wide availability of human enhancement methods, but Zero K draws attention to wealth as the demarcation line between those who can choose to enjoy the benefits of technology and those who remain excluded regardless of their choice. In this context, Zero K confronts the potential of cryopreservation with reality and draws attention to points of tension within the transhumanist approach to ageing.